A LITERATURE REVIEW ON THE CURRENT STATE-OF-THE-ART METHODS IN THE TREATMENT OF ATYPICAL DERMATITIS - Latipov Ikhtiyor Ikromovich; Rakhimov Otabek Khujamberdiyevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The problem of atopic dermatitis is becoming increasingly important in modern medicine. In the structure of allergic diseases in children, atopic dermatitis occupies one of the leading places in terms of its prevalence. However, many issues of this problem still remain unresolved. The article presents a review of the literature of domestic and foreign authors, summarizing modern ideas about the classification, approaches to the treatment and prevention of atopic dermatitis.